2021
DOI: 10.3390/land10101057
|View full text |Cite
|
Sign up to set email alerts
|

Plant Trait Assembly in Species-Rich Forests at Varying Elevations in the Northwest Andes of Colombia

Abstract: Andean forests are home to a strikingly high diversity of plants, making it difficult to understand the main drivers of species assembly. Trait-based approaches, however, help overcome some challenges associated with high taxonomic complexity, providing insights into the main drivers of species coexistence. Here, we evaluated the roles of climate, soil fertility, and symbiotic root associations on shaping the assembly of six plant functional traits (leaf area, specific leaf area, dry leaf matter content, leaf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…The structural trait values (LMA, LT, LDMC, LA and LW) on an absolute basis for cold-affiliated species at the 14°C site are of the same order of magnitude as those reported at high-elevation sites in adult trees along other elevation gradient studies in the Andes (Bahar et al, 2017;Llerena-Zambrano et al, 2021;Martin et al, 2020;Ochoa-Beltrán et al, 2021;van de Weg et al, 2009), and in TMF in Rwanda from both adult (Mujawamariya et al, 2018) and juvenile trees (Dusenge et al, 2021;Manishimwe et al, 2022). The much higher LT (and LMA) values for C. multiflora could be attributed to Clusia's relation to C 3 /crassulacean acid metabolism (CAM) behaviour (Grams et al, 1998;Lüttge, 2006), where water-efficiency traits, such as larger vacuoles and fewer leaf internal air spaces, have been conserved across the genus (Barrera Zambrano et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The structural trait values (LMA, LT, LDMC, LA and LW) on an absolute basis for cold-affiliated species at the 14°C site are of the same order of magnitude as those reported at high-elevation sites in adult trees along other elevation gradient studies in the Andes (Bahar et al, 2017;Llerena-Zambrano et al, 2021;Martin et al, 2020;Ochoa-Beltrán et al, 2021;van de Weg et al, 2009), and in TMF in Rwanda from both adult (Mujawamariya et al, 2018) and juvenile trees (Dusenge et al, 2021;Manishimwe et al, 2022). The much higher LT (and LMA) values for C. multiflora could be attributed to Clusia's relation to C 3 /crassulacean acid metabolism (CAM) behaviour (Grams et al, 1998;Lüttge, 2006), where water-efficiency traits, such as larger vacuoles and fewer leaf internal air spaces, have been conserved across the genus (Barrera Zambrano et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
“…In the tropical Andes, community‐level measurements of structural traits such as LA and LW, have been shown to increase or remain similar with warming/decreasing elevation, while LT decreases to give lower LMA values at warmer, lower elevations (Homeier et al, 2021; Llerena‐Zambrano et al, 2021; Martin et al, 2020; Ochoa‐Beltrán et al, 2021; van de Weg et al, 2009). Foliar N and P contents expressed in dry weight basis ( N m and P m ) have often been found to be higher in lowland forests than those in the cooler highlands, while values expressed in leaf area basis ( N a and P a ) have shown less clear patterns of variation with elevation (Homeier et al, 2021; Martin et al, 2020; van de Weg et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the functional composition along the PC1 _climate were de- in the lowlands to conservative strategies in the highlands. These trends are widely reported in tropical mountain forests (Homeier et al, 2021;Maharjan et al, 2021;Ochoa-Beltrán et al, 2021) and are related to a gradient of the leaf resource investment and return (Wright et al, 2004).…”
Section: Variation In Functional Composition Along the Elevational Gr...mentioning
confidence: 70%
“…In mountain systems, the variation in functional composition has been studied primarily by evaluating how functional traits change along a natural gradient of temperature with elevation increase (Homeier et al., 2021; Ochoa‐Beltrán et al., 2021). These studies have found that tree communities along elevational gradients tend to vary from acquisitive strategies (plants with fast‐growth rates and low construction costs) in lowlands to conservative strategies (plants with high construction costs) in highlands (Maharjan et al., 2021; Ochoa‐Beltrán et al., 2021). However, the temporal change in the functional composition of plant communities in response to changes in climatic conditions remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%